How to feed the world in 2050: actions in a changing climate - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
World Scientists Urge Key Actions for Achieving Food Security in a Changing Climate https://ccafs.cgiar.org/commission/reports/ To achieve food security in a changing climate, the global community must operate within three limits: the quantity of food that can be produced under a given climate; the quantity needed by a growing and changing population; and the effect of food production on the climate. At present the planet operates outside that safe space, as witnessed by the enormous number of people who are undernourished. If current trends in population growth, diets, crop yields and climate change continue, the world will still be outside this 'safe operating space' in 2050. Humanity must urgently work to enlarge the safe space and also move the planet into the safe space. The Commission on Sustainable Agriculture and Climate Change has a produced a set of concrete policy actions to transform the food system. Credits: Concept developed by the Commission on Sustainable Agriculture and Climate Change, in collaboration with University of Minnesota Global Landscapes Initiative. Animation and editing: Diego Maclean Music: Adam Lastiwka Voice: Adam Beauchesne